2004
DOI: 10.1139/f04-161
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in acoustic densities: why do we see less in the dark?

Abstract: Diurnal fluctuations in total integrated echo abundance and in vertical density profiles were examined using data from the Norwegian combined acoustic and bottom-trawl survey for demersal fish during winter in the Barents Sea. The total echo abundance was about 40%-50% higher at day than at night. An unknown amount of fish was lost close to the seabed in the acoustic dead zone, but the systematic changes in the near-bottom vertical density profiles did not indicate that migration in and out of the dead zone wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…All surveys began after daybreak and concluded before dusk. Some fish species, particularly herring, undergo diurnal migrations through the water column that can affect acoustic density estimates (Huse and Korneliussen, 2000;Hjellvik et al, 2004). We chose to sample only during daylight because of the diel variation in acoustic density estimates and to facilitate observations of foraging sea lions while collecting acoustic data.…”
Section: Acoustic Surveysmentioning
confidence: 99%
“…All surveys began after daybreak and concluded before dusk. Some fish species, particularly herring, undergo diurnal migrations through the water column that can affect acoustic density estimates (Huse and Korneliussen, 2000;Hjellvik et al, 2004). We chose to sample only during daylight because of the diel variation in acoustic density estimates and to facilitate observations of foraging sea lions while collecting acoustic data.…”
Section: Acoustic Surveysmentioning
confidence: 99%
“…The vertical positioning of cod therefore potentially has a great impact on measurements of cod. Hjellvik et al (2004) found that the acoustic abundance of fish in the Barents Sea was two times higher during the day than at night and attributed this difference to diurnal differences in vertical distribution and tilt of the fish. Although their study was based on aggregated data and not only cod, it illustrates the importance of considering fish behaviour in stock assessment.…”
Section: Implications For Stock Assessment and Further Workmentioning
confidence: 99%
“…Describing such aggregative patterns is essential to modelling of the in situ schooling behaviour of fish (Azzali et al 1985, Viscido et al 2004. Schooling behaviour must be considered in the management of fisheries of pelagic species because of its impact on the estimation of catchability coefficients (Marchal & Petitgas 1993, Hjellvik et al 2004. Nevertheless, in situ measurements of basic behaviour, such as schooling and diel aggregative patterns, are complex to obtain and to interpret.…”
Section: Introductionmentioning
confidence: 99%